Formação da identidade docente : estágio supervisionado, memórias e representações sociais. - Oliveira, Sandra Mara Vieira (2011)
This research analyses the knowledge, memory and social representation of teachers of UESB Practice Teaching Degree in Geography relation to the experience of supervised practice in their initial training, highlighting the contribution of this experience for the construction of their professional identities. The methodological option fell on the qualitative approach through case study, with reference to oral history. The fieldwork took place at the Universidade Estadual do Sudoeste da Bahia - UESB campus of Vitoria da Conquista. It integrates the research population eight (08) teachers in the area of Teaching Degree in Geography. Different sources report the results: a) Bibliographical review on theoretical categories relevant to the object of research, b) Documentary sources: archives, publications on supervised training, the National Curriculum Guidelines, Course Plan of the discipline Teaching Practice and Educational Project Course Degree in Geography UESB, among others; the emphasis was Oral Sources - with the realization of (06) interviews with teachers who over their course trajectory have taught the discipline of Teaching Practice. This paper first analyzes the process of institutionalization of the Brazilian schooling in the nineteenth and twentieth centuries, as well as the genesis of higher education in Brazil, with emphasis on the origin of degrees and particularly a degree in Geography. Following it discusses the importance of knowledge, memories and social representation in the teaching profession, contextualizes the research scene from an analysis of the historical context of Vitoria da Conquista city, the creation of the Universidade Estadual do Sudoeste da Bahia - UESB and the trajectory of the Full Bachelor's Degree in Geography of that institution. Finally it analyzes the course of the study subjects in relation to their past experience as students of a training course and currently as teachers who are experiencing the social practices in their exercise of teaching in higher education. It is observed in the testimonies of respondents strongly influence of people's family to motivate them to choose teaching. It stands out a common point among those interviewed emphasized: the difficulties encountered at the beginning of the teaching profession, as a function of intellectual immaturity. The initial training, the experience of stage and everyday experiences developed in the paths as teachers helped to overcome these barriers. In this sense, knowledge of mastership, which combine training and teaching experience, covering not only disciplinary knowledge, but also the know-how, skills and abilities that found the work of teachers in the classroom. practice